2017
DOI: 10.1186/s12871-017-0333-3
|View full text |Cite
|
Sign up to set email alerts
|

Changes in intraocular pressure and optic nerve sheath diameter in patients undergoing robotic-assisted laparoscopic prostatectomy in steep 45° Trendelenburg position

Abstract: BackgroundTo evaluate changes in intraocular pressure (IOP) and intracerebral pressure (ICP) reflected by the optic nerve sheath diameter (ONSD) in patients undergoing robotic-assisted laparoscopic prostatectomy (RALP) in permanent 45° steep Trendelenburg position (STP).MethodsFifty-one patients undergoing RALP under a standardised anaesthesia. IOP was perioperatively measured in awake patients (T0) and IOP and ONSD 20 min after induction of anaesthesia (T1), after insufflation of the abdomen in supine positio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
32
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 24 publications
4
32
0
1
Order By: Relevance
“…To the best of our knowledge, the present study was the first and largest prospective study to evaluate IOP and visual field sensitivity during RALP in the patients with ocular diseases. We showed that IOP significantly increased during TP in RALP in a time‐dependent manner, as previously described . Regarding the degree of elevation of IOP, at 3 h after TP, glaucomatous patients showed significantly lower IOP change, partly because of perioperative ophthalmic drops to maintain IOP within the normal range.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…To the best of our knowledge, the present study was the first and largest prospective study to evaluate IOP and visual field sensitivity during RALP in the patients with ocular diseases. We showed that IOP significantly increased during TP in RALP in a time‐dependent manner, as previously described . Regarding the degree of elevation of IOP, at 3 h after TP, glaucomatous patients showed significantly lower IOP change, partly because of perioperative ophthalmic drops to maintain IOP within the normal range.…”
Section: Discussionsupporting
confidence: 83%
“…We showed that IOP significantly increased during TP in RALP in a time-dependent manner, as previously described. [5][6][7][8]13,20 Regarding the degree of elevation of IOP, at 3 h after TP, glaucomatous patients showed significantly lower IOP change, partly because of perioperative ophthalmic drops to maintain IOP within the normal range. At 7 days after RALP, IOP returned to near preoperative levels, as previously described.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Observational studies have reported impairment of cerebrovascular autoregulation and increased intracranial pressure during surgery in the Trendelenburg position with capnoperitoneum . Ischemic optic neuropathy resulting from intracranial pressure elevation has been observed in single cases during Trendelenburg position …”
Section: Discussionmentioning
confidence: 99%